1964
DOI: 10.1139/o64-044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Estradiol and Testosterone on the Fatty Acids of Plasma Cholesteryl Esters and Phospholipids in the Castrated Rat

Abstract: The effects of physiological doses of estradiol and testosterone on plasma cholesteryl ester and phospholipid fatty acid composition were investigated in castrated male rats. The animals were killed after 3 weeks on experiment, and their plasma cholesteryl esters and phospholipids were analyzed and coinpared with those of intact female and male rats.Estradiol appeared to be responsible for the increased proportion of plasma cholesteryl arachidonate seen in the female or estrogen-injected rats since the proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1965
1965
1978
1978

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…22:6) (21). In the Serum lipids and fotw m i d composition of serum lecithin 5 animal, in vivo and in vitro studies indicate that pathway I1 is more active in the female (17, 26) as well as during estrogen administration (18). Studies during the menstrual cycle in young women suggest that this influence by estrogens on pathway I1 is applicable also in man (10).…”
Section: Discussionmentioning
confidence: 99%
“…22:6) (21). In the Serum lipids and fotw m i d composition of serum lecithin 5 animal, in vivo and in vitro studies indicate that pathway I1 is more active in the female (17, 26) as well as during estrogen administration (18). Studies during the menstrual cycle in young women suggest that this influence by estrogens on pathway I1 is applicable also in man (10).…”
Section: Discussionmentioning
confidence: 99%
“…The relative decrease of sphingomyelin is in accordance with the findings in pregnancy, but an absolute increase of sphingomyelin was found by Jensen only in some of the cases. Lyman et al (40) found no effect on the phospholipid pattern in castrated rats which were treated with small physiological doses of estradiol; but the effect of large doses comparable to the amounts produced during pregnancy was not studied. In a recent paper (27) the effect of small doses of conjugated equine estrogens on the serum phospholipids in post-menopausal women was reported.…”
Section: Discussionmentioning
confidence: 99%
“…Depending upon the sex of the animal, chronic ethanol ingestion affects the oxidation of certain mitochondrial substrates differently (1,2)o These differences have been related to the male sex hormone, testosterone (2). In studies not related to ethanol ingestion, estradiol and testosterone have been shown to affect the biosynthesis of phosphatidylcholine (PC) (3,4). Other researchers (5-7) have reported sex differences in total liver lipid composition as well as in liver lipid metabolism (4,(8)(9)(10)(11), and a fractionation of liver PC has shown sex differences in certain molecular species of PC (12).…”
Section: Introductionmentioning
confidence: 99%